Effect of Codoping Zinc Oxide Nanoparticles with Sulfur and Nitrogen on Its Energy Bandgap, Antioxidant Properties, and Antibacterial Activity - Diriba Yadesa; Jabessa Nagasa Guyasa; Tamene Tadesse Beyene (Advances in Materials Science and Engineering)
Zinc oxide nanoparticles (ZnO-NPs) are used in various fields such as industrial, environmental remediation, catalytic, and antibacterial applications. However, their ability to absorb visible light is limited due to their high-energy bandgap and fast electron-hole recombination, which restricts their use. To enhance the efficiency of ZnO-NPs in medical and other applications, surface functionality can be modified through doping. Here, we investigated the effects of S and N doping on the energy bandgap of ZnO-NP and their antimicrobial and antioxidant activities. The results showed that the optical bandgap energy of pure ZnO-NPs was 2.98 eV while that of 6% N-ZnO, 4% S-ZnO, and S4-N6-ZnO was 2.78, 2.69, and 2.63 eV, respectively. The energy bandgap reduction is attributed to the changes in the electronic level of zinc oxide as the result of doping. The crystal size of pure ZnO-NPs, 6% N-ZnO, 4% S-ZnO, and S4-N6-ZnO was 29.06, 27.05, 29.02, and 25.06 nm, respectively, as calculated from XRD data using FWHM. Following the bandgap and particle size reduction, the antimicrobial activities of the dual-doped ZnO-NPs surpassed that of the pure ZnO-NPs. Moreover, dual doping improved the antioxidant activity of ZnO-NPs from 52.45% to 88.89% for the optimized concentration. Therefore, incorporating S and N as dual dopants can enhance the functionality and efficiency of ZnO-NPs in various fields.